Flow Velocity Distribution Analysis On Free Intake Structure And Its Influence To Intake Capacity - Bakri B; Pallu S; Lopa R; Akbar M; Ihsan M; Arai Y (International Conference on Engineering and Technology Development (ICETD), 2017)
As maritime state, most of Indonesian reside in coastal areas or estuaries, leading sanitation and water supply a major concern of the people. The use of groundwater with considerably limited amount is more limited due to seawater intrusions. On the other side, surplus of freshwater from upstream is very abundant near the estuaries. However, morphological condition of river downstream or in estuaries with huge dimension and depth causes expensive cost in order to utilize freshwater in estuaries. One of the solutions to utilize water downstream or near estuaries as raw water for clean water is to build free intakes around river estuaries. However, as the utilizing proceeding, it is found a problem that intake capacity is far below their design capacity. The research is an experimental research conducted in the laboratory which aimed to investigate the relationship of flow velocity distribution on no free intake and with free intake condition and its influence to the capacity of free intake structures.  The result shows that either on no free intake and with free intake condition minimum velocity occurs around channel bed and increasing upright and decreasing again when approaching surface of the channel. The positioning of intake pipe is highly influencing intake capacity. Maximum condition is achieved when intake pipe is positioned on channel bed and near channel surface while minimum condition is achieved when pipe is around middle part of the channel. Keywords—Free intake: velocity distribution: intake capacity.